2011
DOI: 10.1109/tac.2010.2090707
|View full text |Cite
|
Sign up to set email alerts
|

Robust Filtering Through Coherent Lower Previsions

Abstract: Abstract-The classical filtering problem is re-examined to take into account imprecision in the knowledge about the probabilistic relationships involved. Imprecision is modeled in this paper by closed convex sets of probabilities. We derive a solution of the state estimation problem under such a framework that is very general: it can deal with any closed convex set of probability distributions used to characterize uncertainty in the prior, likelihood, and state transition models. This is made possible by formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 32 publications
0
38
0
Order By: Relevance
“…Antonucci et al [34] investigated the use of iHMMs under epistemic irrelevance for tracking tasks. Benavoli et al [8] defined an iHMM over continuous variables aimed at robust filtering. An imprecise version of the Baum-Welch procedure [1], used to estimate the parameters of an HMM when the state sequence is not observable, was developed by Antonucci et al [35], and tested on an activity recognition task.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Antonucci et al [34] investigated the use of iHMMs under epistemic irrelevance for tracking tasks. Benavoli et al [8] defined an iHMM over continuous variables aimed at robust filtering. An imprecise version of the Baum-Welch procedure [1], used to estimate the parameters of an HMM when the state sequence is not observable, was developed by Antonucci et al [35], and tested on an activity recognition task.…”
Section: Related Workmentioning
confidence: 99%
“…This is the case, for instance, when data are scarce [5], observations are missing not-at-random [6], and information is conflicting. In such cases, the use of probability distributions to represent uncertainty might be inadequate and lead to overly confident inferences [5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Such a state estimate can neither be described by a single probability function nor by a single set. To solve this issue, we make use of the theory of imprecise probabilities [10], from which generalizations of Bayesian state estimation have, for example, been derived in [11,12]. For our purpose of bounding linearization errors within the Kalman filtering framework, sets of probability densities [13,14] will serve as proper characterizations of uncertain quantities.…”
Section: Sets Of Densitiesmentioning
confidence: 99%
“…The covariance of the set of estimated Gaussian densities is still given by the standard equation (11). Because of the linearization, this matrix still can be underestimated, but the set of means, i.e., the bounds for linearization errors, enables us to compute a guaranteed confidence set with respect to the a priori defined probability level P .…”
Section: Filteringmentioning
confidence: 99%
“…Recent work (De Cooman, Hermans, Antonucci, & Zaffalon, 2010) has shown that the use of epistemic irrelevance guarantees that there is an efficient algorithm for updating beliefs about a single target node of a credal tree, that is essentially linear in the number of nodes in the tree. For imprecise-probabilistic hidden Markov models (iHMMs), which are the credal network equivalent of hidden Markov models (HMMs), this efficiency for single target node inferences has been succesfully exploited to develop an imprecise-probabilistic counterpart to the Kalman filter (Benavoli, Zaffalon, & Miranda, 2011).…”
Section: Introductionmentioning
confidence: 99%